Systematic Literature Review: Model Problem Based Learning pada Pembelajaran Matematika Sekolah Dasar - Elfiyani, Elfiyani (Asian Journal of Early Childhood and Elementary Education, 2024)
This research presents a comprehensive picture of the positive impact of the Problem Based Learning (PBL) model on mathematics learning in elementary schools. Through the Systematic Literature Review method, the research identified 10 relevant articles that reinforce the findings on the effectiveness of PBL in improving the quality of mathematics learning. Analysis of the articles showed that PBL consistently improves various aspects of learning, including improved cognitive ability, problem-solving ability, better learning outcomes, communication of ideas, and learner character development. These findings provide a deeper understanding of the potential of PBL as a learning method that is not only alternative, but also highly effective in improving mathematics learning in primary schools. As a result, this study makes an important contribution in strengthening support for the use of PBL in the context of mathematics education at the primary level.